2012
DOI: 10.3390/molecules171112771
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants: A Source of Anti-Parasitic Secondary Metabolites

Abstract: This review summarizes human infections caused by endoparasites, including protozoa, nematodes, trematodes, and cestodes, which affect more than 30% of the human population, and medicinal plants of potential use in their treatment. Because vaccinations do not work in most instances and the parasites have sometimes become resistant to the available synthetic therapeutics, it is important to search for alternative sources of anti-parasitic drugs. Plants produce a high diversity of secondary metabolites with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
217
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(224 citation statements)
references
References 61 publications
2
217
0
5
Order By: Relevance
“…Alternatively, other natural products from different sources could be tested. These could include microbial products of activated cryptic pathways (see elsewhere in this review) or secondary metabolites from plants [207][208][209][210][211][212] , endophytic fungi 213 , or marine sources 214 .…”
Section: Opportunities For Natural Productsmentioning
confidence: 99%
“…Alternatively, other natural products from different sources could be tested. These could include microbial products of activated cryptic pathways (see elsewhere in this review) or secondary metabolites from plants [207][208][209][210][211][212] , endophytic fungi 213 , or marine sources 214 .…”
Section: Opportunities For Natural Productsmentioning
confidence: 99%
“…Furthermore, even if animal experiments were successful, we would need clinical trials of the new compounds alone or in combination with established parasiticidal drugs to prove their efficacy and safety. These developments are costly and it is presently difficult to attract the pharmaceutical industries into these fields for various reasons [20]. The objective of the present work was to investigate the in vitro anthelmintic efficacy of solvent extracts of M.fraxinea Sm.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that alkaloids, flavonoids, chalcones, terpenoids, saponins, and phenolic compounds display antileishmanial effect (Sandjo et al, 2016;Singh et al, 2014;Wink, 2012). In the present study, HPLC-DAD was employed to evaluate the phytochemical profile of Q2.…”
Section: Discussionmentioning
confidence: 99%